2011
DOI: 10.5847/wjem.j.1920-8642.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Demand for hospital emergency departments: a conceptual understanding

Abstract: This review has explored the factors contributing to the growing demand for ED care, the influence these factors have on ED demand, and their interrelationships depicted in the conceptual model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 89 publications
0
39
0
Order By: Relevance
“…In a systematic review of the literature examining the demand for hospital EDs, He et al (2011) show that in general, older people are more likely to use EDs for urgent medical conditions, while younger people tend to present more frequently to EDs for injury and less-urgent illness such as fever, cough, nausea or vomiting.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of the literature examining the demand for hospital EDs, He et al (2011) show that in general, older people are more likely to use EDs for urgent medical conditions, while younger people tend to present more frequently to EDs for injury and less-urgent illness such as fever, cough, nausea or vomiting.…”
mentioning
confidence: 99%
“…In a systematic review of 100 studies, He et al (2011) found that social support plays a significant role in ED demand. The relationship appears particularly strong for elderly patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, private hospital EDs has the potential to alleviate the pressure in the public system. (He, 2012;He et al, 2011), and below is a summary of these results:…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focussed on identifying the factors that influence the demand for emergency service (He, Hou, Toloo, Patrick, & Fitzgerald, 2011) and establishing a theoretical framework for emergency service demand (Toloo et al, 2011b). However, no research has been conducted to understand the factors that influence patients' choice between public and private EDs.This study seeks to fill this gap.…”
Section: Private Hospital Eds and What Factors Influence Their Decisimentioning
confidence: 99%